The Case of Alternative Versus Traditional Financing: A Literature Review - Obiora, Sandra Chukwudumebi; Csordás, Tamás (Archives of Business Research, 2017)
Receiving a loan from the bank has in the recent decades become a more difficult procedure with a gradually worsening percentage rate of loan application successes. Small and commercial banks are faced with several external challenges and pressures that affect their lending behaviors and force them to ration credit. Thus, they employ the cookie cutter approach to screening loan applications which tend to leave the borrowers at a greater disadvantage. Even worse, Small and Medium-sized Enterprises who are often in great need of start-up capital are faced with not just the progressively strenuous process of putting in an application at the bank for a loan which by itself goes beyond a day, but also a high chance of its rejection. On the other hand, alternative financing methods in the form of peer to peer lending, crowdfunding, and other online platforms come not just with a different level of ease of applications, but also several marketable benefits for the entrepreneur. This paper works to offer an unbiased and wider view of the current state of alternative financing growth (with a case study from China) while contrasting it with the situation of bank lending and the different levels of ease of loan access the alternative procedures offer. Also, it exposes not just upon the innovation and growing list of advantages of alternative financing, but also the risks involved for the lenders, and how risk is allocated. Finally, the paper presents an insight into the future of the alternative financing market.